Quorum sensing regulators and non-ribosomal peptide synthetases govern antibacterial secretions in Xenorhabdus szentirmaii - Dey, Ritisha; Valle, Domonique Olivia; Chakraborty, Abhijit; Mayer, Kimberly A.; Uppala, Jagadeesh Kumar; Chakraborty, Anish; Mirza, Shama; Skwor, Troy; Forst, Steven; Dey, Madhusudan (Frontiers in Microbiology, 2025)
The decades-long gap in antibiotic discovery has led to a significant health crisis due to antimicrobial resistance (AMR). The bacterial genus Xenorhabdus, which forms symbiotic relationships with the soil nematode Steinernema, are known to secrete a variety of antimicrobial compounds with potential effectiveness against AMR. These antimicrobial compounds are primarily bio-synthesized by non-ribosomal peptide synthetases (NRPS) and polyketide synthase (PKS) genes. In this study, we report that X. szentirmaii produces high levels of antibiotic activity during the stationary phase against diverse bacteria including known antibiotic resistant pathogens. It possesses 17 operons to encode predicted NRPS and PKS enzymes, designated as ste1 through ste17. The ste15-ste16 and ste17 operons are predicted to produce the known antibiotics Pax peptide and Fabclavine, respectively. Additionally, the newly identified operons ste3, ste4, ste5, ste8, ste9, and ste14 consist of single genes, each containing two or more NRPS genes. The ste13 operon harbors two NRPS genes, while the ste7 and ste12 operons contain three NRPS genes each. Further, RNA-seq analysis showed that lsrF that encodes a quorum sensing autoinducer-2 (AI-2) thiolase was expressed at high levels during stationary phase. These findings provide evidence that X. szentirmaii uses quorum sensing (QS) to synchronize the expression of multiple NRPS and PKS enzymes responsible for synthesizing various antimicrobial compounds. This study underscores the potential to leverage these regulatory insights for maximizing commercial applications of novel antibiotics combating AMR, as well as broader industrial uses.